Estimates for Approximation Characteristics of the Besov Classes $B_ r^{p,θ}$ of Periodic Functions of Many Variables in the Space $L_q. I$ - Romanyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We obtain order estimates for the approximation of the classes $B_ r^{p,θ}$ of periodic functions of many variables in the space $L_q$ by using operators of orthogonal projection and linear operators satisfying certain conditions.